Axial Load Variation of Columns in Symmetrical RC Buildings Subject to Bidirectional Lateral Actions in Regions of Low to Moderate Seismicity. Issue 5 (4th April 2022) - Raza, S.; Menegon, Scott J.; Tsang, Hing-Ho; Wilson, John L.
ABSTRACT: Columns in building frame systems are subjected to the combined action of bidirectional horizontal loading and axial load variation during an earthquake. Whilst the behaviour of RC columns under unidirectional and bidirectional lateral loading with constant axial load is understood well, the behaviour under bidirectional lateral loading with axial load variation is rarely studied, especially for limited ductile RC columns prevalent in regions of low to moderate seismicity. This paper begins with a numerical study that aims to obtain the generalised patterns and range of axial load variation in RC building columns. To this end, a case study building is subjected to a suite of 15 ground motions, representative of low to moderate seismic regions, in OpenSees. This is followed by an experimental study in which limited ductile high-strength RC columns are tested under bidirectional lateral loading and two different axial load variation protocols, namely synchronous and nonsynchronous variable axial loading protocols. The results of the numerical study demonstrated that axial load variation of the columns in an RC building is primarily dependent on the response spectral acceleration corresponding to the fundamental period of the structure in the two orthogonal horizontal directions and/or the vertical direction. The results of the experimental testing showed that nonsynchronous axial loading (compared to constant and synchronous axial loading) results in the lowest collapse drift capacity and energy dissipation of the RC columns.